New replacement name for Anaperus Graff, 1911 (Acoelomorpha: Acoela: Convolutidae) - Hernández, J. A. Rivaz (Zootaxa, 2018)
The acoel genus Anaperus was established by Graff in 1911 for Amphiscolops gardineri Graff, 1910, making Anaperus gardineri (Graff, 1910) its type species. Since then, six more valid species were described: A. tvaerminnensis (Luther, 1912); A. sulcatus Beklemischev, 1914; A. rubellus Westblad, 1945; A. biaculeatus Boguta, 1970; A. ornatus Beltagi, 2001; A. singularis Hooge & Smith, 2004. A seventh species, A. australis Westblad, 1952, is incertae sedis (Dörjes & Karling, 1975). The genus was placed to family Convolutidae Graff, 1905, until Dörjes (1968) erected the family Anaperidae on the basis of a distinctive male copulatory apparatus. Jondelius et al. (2011) returned it to Convolutidae on the basis of molecular–sequence data.